First Imported Case of Chikungunya Virus Infection in a Travelling Canadian Returning from the Caribbean - Christian Therrien; Guillaume Jourdan; Kimberly Holloway; Cécile Tremblay; Michael A. Drebot (Canadian Journal of Infectious Diseases and Medical Microbiology)
This is the first Canadian case of Chikungunya virus (CHIKV) infection reported in a traveller returning from the Caribbean. Following multiple mosquito bites in Martinique Island in January 2014, the patient presented with high fever, headaches, arthralgia on both hands and feet, and a rash on the trunk upon his return to Canada. Initial serological testing for dengue virus infection was negative. Support therapy with nonsteroidal anti-inflammatory drugs was administered. The symptoms gradually improved 4 weeks after onset with residual arthralgia and morning joint stiffness. This clinical feature prompted the clinician to request CHIKV virus serology which was found to be positive for the presence of IgM and neutralizing antibodies. In 2014, over four hundred confirmed CHIKV infection cases were diagnosed in Canadian travellers returning from the Caribbean and Central America. Clinical suspicion of CHIKV or dengue virus infections should be considered in febrile patients with arthralgia returning from the recently CHIKV endemic countries of the Americas.